Performance Analysis of NOMA in Drone Communication - Ayranci, Ahmet Aytug; Bacanli, Emre; Ilhan, Haci (IEEE, 2019)
As wireless communication technology has been advanced and the number of devices that requires wireless connection has been increased, it creates a massive demand for ubiquitous coverage, high data rate, and greater capacity. Drone communication with Non-Orthogonal Multiple Access (NOMA) can be a solution for these demands entirely. Drones can be used as aerial base stations with their high mobility, and better coverage provides communication whenever and wherever it's required. Also, NOMA has several advantages over conventional Orthogonal Multiple Access (OMA) techniques. These advantages are spectral efficiency, low latency, and better sum rate. These advantages make the NOMA perfect solution for today's communication demands in 5G and beyond. In this paper, the performance of NOMA in drone communication is investigated. Individually, the capacity and fairness index's changes in the considered system with different power allocation (PA) schemes have been examined.
Keywords: Engineering